Separation of Heat-Stable Antifungal Factor From Lysobacter enzymogenes Fermentation Broth via Photodegradation and Macroporous Resin Adsorption - Tang, Bao; Wu, Lingtian; Wang, Jinzi; Sun, Weibo; Zhao, Yancun; Liu, Fengquan (Frontiers in Microbiology, 2021)
Heat-stable antifungal factor (HSAF) is produced by the fermentation of Lysobacter enzymogenes, which is known for its broad-spectrum antifungal activity and novel mode of action. However, studies on the separation of HSAF have rarely been reported. Herein, alteramide B (the main byproduct) was removed firstly from the fermentation broth by photodegradation to improve the purity of HSAF. Then, the separation of HSAF via adsorption by macroporous adsorption resins (MARs) was evaluated and NKA resin showed highest static adsorption and desorption performances. After optimizing the static and dynamic adsorption characteristics, the content of HSAF in the purified product increased from 8.67 ± 0.32% (ethyl acetate extraction) to 31.07 ± 1.12% by 3.58-fold. These results suggest that the developed strategy via photodegradation and macroporous resin adsorption is an effective process for the separation of HSAF, and it is also a promising method for the large-scale preparation of HSAF for agricultural applications.